Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.4300/jgme-d-11-00135.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Medical Liability Crisis on Postresidency Training and Practice Decisions in Obstetrics-Gynecology

Abstract: Concerns about medical malpractice and the medical liability crisis are not new. Their impact on the field of obstetrics and gynecology has been discussed since the 1970s and 1980s.1 Evaluations of the specific bearing of the liability crisis on obstetricians and gynecologists have demonstrated regional influence on providers.2,3 Nationally, more than 60% of obstetricians and gynecologists have made one or more changes to their practices as a result of the affordability or availability (or both) of professiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
(4 reference statements)
0
7
0
Order By: Relevance
“…Current data suggest that medico-legal training during OBGYN residency is inadequate (15) . A large survey study showed that more than 20% of the fourth-year OBGYN residents had already been in a lawsuit (16) and more than half of those indicated that they had not received adequate training on legal matters. In a prospective survey study, 35% of residents stated that they had been planning for a fellowship program only because of malpractice concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Current data suggest that medico-legal training during OBGYN residency is inadequate (15) . A large survey study showed that more than 20% of the fourth-year OBGYN residents had already been in a lawsuit (16) and more than half of those indicated that they had not received adequate training on legal matters. In a prospective survey study, 35% of residents stated that they had been planning for a fellowship program only because of malpractice concerns.…”
Section: Discussionmentioning
confidence: 99%
“… 10 The Accreditation Council for Graduate Medical Education requires a minimum of 15 TVH out of a total of 70 minimally invasive hysterectomies. 25 The small proportion of required TVH cases compared with the total minimally invasive hysterectomies created the potential for potentially choosing laparoscopic routes over vaginal hysterectomy in future practice.…”
Section: Dynamics Of Minimally Invasive Gynecologic Surgery Costsmentioning
confidence: 99%
“… 25 Half of graduating residents receive no formal training in risk management when it comes to medical liability, yet more than 20% of residents are already involved in a lawsuit by graduation. 25 According to a nationwide survey of residency program directors in 2005, the average number of medicolegal didactic sessions for residents is only four per year. 25 This did not improve after 15 years according to another survey in 2020.…”
Section: Dynamics Of Minimally Invasive Gynecologic Surgery Costsmentioning
confidence: 99%
“…Studies show that residents and medical students identify liability-related issues as a major factor in considering post-residency work [ 4 , 5 , 6 ]. However, residency training lacks sufficient medicolegal education, exacerbating trainee fear [ 7 ].…”
Section: Introductionmentioning
confidence: 99%